Tax Sanctions as a Moderation Variable That Influencing Fiscus Services, Implementation of E-Filing, and Tax Audit on Taxpayer Compliance - WAFA, Moh. Ali; KUSMAYASARI, Dewi; DARMAYANTI, Novi (Journal of Governance, Taxation and Auditing, 2024)
Taxes play a crucial role as one of the primary sources of government revenue, significantly impacting essential sectors such as education, healthcare, and infrastructure. This research aims to analyze the influence of tax authorities' services, the implementation of e-filing, and tax audits on taxpayer compliance at KPP Pratama Lamongan, with tax sanctions as a moderating variable. The research method used is quantitative by collecting primary data through questionnaires distributed to taxpayers. The results of the research show that there is a significant influence of tax authorities' services and the implementation of e-filing on taxpayer compliance. Apart from that, tax audits also contribute to increasing compliance. Tax sanctions are proven to strengthen the relationship between the independent and dependent variables. This research provides an important contribution to the development of tax policy and strategies for increasing taxpayer compliance in the region. The results of this research can become a reference for further research and help the government in formulating more effective policies.